Flexural performance of FDM-fabricated PLA composites reinforced with short carbon fiber (Fracture and Structural Integrity, 2026)
Adding short carbon fiber reinforcement to thermoplastic matrices can improve the mechanical performance of additively manufactured polymer-based composites. This work examines the flexural behavior of Fused Deposition Modeling (FDM)-produced polylactic acid (PLA)-based composites enhanced by short carbon fibers at 3 wt% and 6 wt%. For comparison, unreinforced PLA specimens were also fabricated under identical processing conditions. All the samples were tested for flexural strength using a three-point bend test, following the ASTM standards for polymer composites. The results showed a clear improvement in strength as the reinforcement content increased. The PLA composite with the 3% short carbon fiber reinforcement showed a noticeable increase in load-bearing ability, while the 6% reinforced composite had an impressive 88% higher flexural strength than the plain PLA. To examine how the materials failed, SEM has been utilized to assess the samples' fractured surfaces.
Keywords: Fused Deposition Modeling; Short Carbon Fiber; PLA Composites; Flexural Strength; Fracture Mechanisms